Comparison of the backbone dynamics of wild-type Hydrogenobacter thermophilus cytochrome c 552 and its b-type variant - Tozawa, K; Ferguson, S; Redfield, C; Smith, L (Springer Verlag, 2015)
© 2015 The Author(s). Cytochrome c 552 from the thermophilic bacterium Hydrogenobacter thermophilus is a typical c-type cytochrome which binds heme covalently via two thioether bonds between the two heme vinyl groups and two cysteine thiol groups in a CXXCH sequence motif. This protein was converted to a b-type cytochrome by substitution of the two cysteine residues by alanines (Tomlinson and Ferguson in Proc Natl Acad Sci USA 97:5156-5160, 2000a). To probe the significance of the covalent attachment of the heme in the c-type protein, 15N relaxation and hydrogen exchange studies have been performed for the wild-type and b-type proteins. The two variants share very similar backbone dynamic properties, both proteins showing high 15N order parameters in the four main helices, with reduced values in an exposed loop region (residues 18-21), and at the C-terminal residue Lys80. Some subtle changes in chemical shift and hydrogen exchange protection are seen between the wild-type and b-type variant proteins, not only for residues at and neighbouring the mutation sites, but also for some residues in the heme binding pocket. Overall, the results suggest that the main role of the covalent linkages between the heme group and the protein chain must be to increase the stability of the protein.